Geopolymer eco-cellular concrete (GECC) based on fluid catalytic cracking catalyst residue (FCC) with addition of recycled aluminium foil powder. (1st December 2017) - Font, Alba; Borrachero, María Victoria; Soriano, Lourdes; Monzó, José; Payá, Jordi
Abstract: This study presents a new cellular concrete design focused on the energy eco-efficiency and the sustainability concept: geopolymer eco-cellular concrete (GECC). Geopolymer systems made from alkali-activated fluid cracking catalyst residue (FCC) aerated by recycled aluminium foil powders (R) were designed. Commercial aluminium powder (A) was also used as an aerating agent in GECC matrix and its effect was compared with traditional cellular concrete (TCC) made with ordinary Portland cement (OPC). The more alkaline medium of the GECC system improved the hydrogen reaction rate and consequently a higher efficiency in the pore matrix development can be found. Aluminium powder addition of 0.2% by mass of the precursor (FCC) was enough to yield cellular concrete with a natural density significantly lower than that found for TCC. The replacement of A by R made it possible to produce an alternative GECC in which the recycling of the waste aluminium has an important eco-efficiency role because its low cost and its energy saving function. Ground R has less aeration effectiveness than A. However, when co-milling of FCC + R was carried out, advantageous performance GECC was attained. Very interesting properties were obtained for this material: good pore size and its proper distribution in the matrix, low natural density (600–700 kg/m 3 ), relatively high compressive strength (2.5–3.5 MPa), low open/closed porosity ratio (1.15) and the lowest thermal conductivity (0.581 W/mK). This opens an interesting way of reusing both FCC as precursor and aluminium foil waste as an aerating agent in the preparation of new geopolymer eco-cellular concrete (GECC). Highlights: Spent fluid catalytic cracking residue FCC was activated and foamed with aluminium. Simple method was designed and tested for quantifying aluminium in powdered samples. The more alkaline medium of the fresh geopolymer improved the hydrogen reaction rate. Co-milling of FCC and aluminium foil waste presented advantageous performance. Low thermal conductivity and natural density for eco-cellular systems were obtained.